Adapting sweet cherry orchards to extreme weather events – Decision Analysis in support of farmers' investments in Central Chile. (February 2021) - Rojas, Gonzalo; Fernandez, Eduardo; Whitney, Cory; Luedeling, Eike; Cuneo, Italo F.
Abstract: Available options for mitigating the impacts of extreme weather events on temperate fruit trees involve a number of risks and uncertainties, leaving growers hesitant about the benefits of implementing new technologies to protect their orchards. We used Decision Analysis approaches, which account for these risks and uncertainties, to assess investment decisions in sweet cherry production systems in central Chile. We evaluated the adoption of polyethylene covers for orchards in northern- and southern-central Chile. Gathering expert and key stakeholder knowledge, we identified relevant variables for the adoption decision and developed a causal impact pathway model. We parameterized this model by collecting estimates from experts in the form of probability distributions. We implemented the model as a Monte Carlo simulation and projected probability distributions for the Net Present Value and the annual cash flow. Results highlight that farmers in southern-central Chile could expect major benefits from covering their orchards, with a 90% confidence interval for the Net Present Value from −33, 605 USD to 595, 447 USD. In northern-central areas, implementing covers did not significantly improve the Net Present Value (90% confidence interval from −149, 597 USD to 433, 361 USD). Across zones, our model results were sensitive to market price, crop yield, and fruit quality problems (i.e. low firmness). Cover effectiveness against rain events was relevant only in the southern-central zone, whereas effectiveness against frost events was relevant in both sites. Expected Value of Perfect Information calculations revealed that additional information on yield and market price could substantially help to make a confident decision. Our simulations suggest that orchard protection in southern-central Chile may be necessary for secure and profitable cherry production in the future. In this case study, we demonstrated the applicability of Decision Analysis to support farmers in identifying appropriate and effective strategies in time to overcome future challenges resulting from climate change. Graphical abstract: Unlabelled Image Highlights: Sweet cherry farmers seek options such as covering orchards to meet challenges related to climate change. Decision Analysis approaches allow assessing these options for complex scenarios. We unpack sweet cherry system complexity and include current knowledge into decision forecasts. Covers may offer major benefits in southern-central but not northern-central Chile. Key variables for this decision are market price, yield and problems related to low fruit firmness.